Changes in Bacterial Soil Biota under Cultivation of Crops near a Municipal Landfill Site - Dariusz Roman Ropek (MDPI AG, 2021)
The study aimed to evaluate the changes in the quantitative composition of a soil bacterial community near a municipal waste landfill, and attempted to use a bacteriological coefficient to assess the degree of soil degradation. The research was carried out near a landfill site located in southern Poland. Soil samples were collected from plots on which spring wheat, field bean and potato were cultivated. Microbiological analyses included the determination of the total number of bacteria in active and dormant (sporulating) stages. The highest ratio of sporulating bacteria in relation to vegetative bacteria was found in the reclaimed sector of the landfill site. The proposed bacteriological indicator of soil quality (i.e., the ratio of the number of sporulating bacteria to the number of vegetative forms) seems to be a good index for the assessment of soil quality near the landfill site.